Control Contable De La Propiedad Planta Y Equipo De La Empresa Megapropinec De La Ciudad De Babahoyo - Contreras Benitez, Mayra Carlota (2019)
This case study entitled ACCOUNTING CONTROL OF THE PROPERTY, PLANT AND EQUIPMENT OF THE COMPANY MEGAPROPINEC OF THE CITY OF BABAHOYO, this is a medium-sized organization dedicated to the commercialization of products of mass consumption, this activity is exercised wholesale and by minor, its capital and sales volume obliges it to keep accounts. In this report, we describe the problems that are arising due to not having an adequate accounting control of the assets that belong to the group of Property, Plant and Equipment, that is, the goods that the company acquires in order to use them. not to sell, as those goods of its main activity and that is considered inventories or merchandise from the accounting point of view. The case study is directly related to the profession, this is the accounting field and is an important part in the formation of the CPA, according to the use and the depreciated values ​​are adjusted annually, until obtaining a residual value that allows to give The asset is properly derecognized without generating loss directly in a specific accounting period, therefore it will not affect the economic result to a fiscal period drastically. and of its line of research, this is accounting and financial management, because the proper accounting of property, plant and equipment assets, allow the good to be written off.